Do elite soccer players cover less distance when their team spent more time in possession of the ball? - Lorenzo-Martinez, M.; Kalén, A.; Rey, E.; López-Del Campo, R.; Resta, R.; Lago-Peñas, C. (Science and Medicine in Football, 2021)
Purpose: The aim of this study was to examine the association between the time spent in possession by teams and the match-running performance in elite soccer matches. Methods: Match performance data were collected from players in Spanish LaLiga (8,468 individual match observations of 412 outfield players) using a multiple-camera computerised tracking system. A k-means cluster analyses classified teams depending on time spent in possession of the ball: very high-percentage ball possession teams (VHPBPT), high-percentage ball possession teams (HPBPT), low-percentage ball possession teams (LPBPT) and very low-percentage ball possession teams (VLPBPT). Results: Overall, physical indicators were highly associated with ball possession. Distances covered in VHPBPT were lower than HPBPT, LPBPT and VLPBPT, especially at low and medium speed. Positionspecific changes were also evident for physical profiles. Attackers (central midfielders, external midfielders and forwards) in VHPBPT covered fewer meters per minute at any speed than their counterparts in HPBPT, LPBPT or VLPBPT. However, defenders (Central defenders and External defenders) in VLPBPT covered lower distances. Conclusion: These findings may have a great deal of practical implications and may help coaches to better understand match-running variations according to ball possession strategies and could be used to develop a model for predicting the physical activity profile in competition.